Peran Notaris Dalam Transaksi Perdagangan Berbasis Elektronik - Rukmana, Rubiyanti; Dwi Savitri, Nandita; Adelvina Padha, Yuliana (Jurnal Komunikasi Hukum, 2021)
The Rapid development of electronics forced notary as a general officer who has the duty to serve the community is expected to be able to respond to the development of this information technology era appropriately. The journal was created to analyze and examine the role of the notary in electronic-based trading transactions. The research method used in the writing of this journal is the normative empirical, which uses secondary data as the primary data and primary data as supporting data. This writing using The approach used is a conceptual approach, a legislative approach, and a comparative approach. The results of the study, the notary must be able to act to authenticate to the parties who conduct transactions of electronic-based trading, verify the documents/information of electronic-based trading that is handled by the parties, securing the electronic document storage in the form of signatures and documents that are signed, but the notary authority in electronic-based trading transactions, for now, can be said to still be a discourse by the Government to be implemented, because The notary authority for making authentic electronic documents in electronic-based trading transactions has no-yet rules of implementing.